Bemagtiging van Verpleegkundiges - 'n Konseptuele Raamwerk - K Jooste (AOSIS, 1999)
An increasing awareness of the value of employees is experienced in health services. Empowerment as a strategy can be used constructively to promote a health services. The problem identified was the absence of a acceptable conceptual framework regarding the concept empowerment. Incomplete and divergent definitions of empowerment were also a concern.